REALISASI PEMBAGIAN HARTA WARISAN KEPADA AHLI WARIS YANG MELEPASKAN HAK WARIS SECARA PAKSA - Michelle Hadlen; Roswita Sitompul; Kartina Pakpahan (Lafadz Jaya Publisher, 2023)
The background of this research is that a will is considered void if it is made under threat or fraud. Threats or fraud can be carried out by parties who want to threaten by alternatively asking the heirs to refuse inheritance or by releasing inheritance rights. The heir who refuses the inheritance is considered never to be an heir because if he dies earlier than the heir, he cannot be replaced by his children who are still alive. The legal research method used in this research is normative juridical research which is research conducted or aimed only at written regulations with the nature of analytical descriptive research which is a method that functions to describe or give an overview of the object under study through data or samples and make general conclusions. Sources of data used in this study are primary and secondary data and analysis of qualitative data which is an observation of phenomena obtained from the data obtained in the form of descriptions, verbal information stated by sources in writing or orally. The result of this research is that provisions for the release of inheritance rights based on the Civil Code (Burgerlijk Wetboek) are regulated in 1057 to 1065 Burgerlijk Wetboek. In Article 1057 Burgerlijk Wetboek states that refusal must be expressly stated in a statement made by the clerk of the District Court in the area where the inherited property is located. Article 1058 Burgerlijk Wetboek states that heirs who refuse inheritance are considered not considered heirs. Article 1059 Burgerlijk Wetboek states that the portion of the inheritance from the person who refuses the inheritance falls into the hands of the person receiving the inheritance. The provisions of the law regarding heirs who are forced to relinquish their inheritance rights are regulated in Article 1065 which states that no one can be fully recovered from refusal of an inheritance, unless the refusal occurs due to fraud or coercion. Settlement of disputes by heirs if coercion occurs can be carried out through litigation, namely through an Unlawful Act lawsuit to the District Court in the area where the inheritance is located.